Managerial ethics and microeconomic theory - Hosmer, LaRue Tone (Journal of business ethics, 1984)
There is a very apparent conflict between economists and ethicists over the moral standards that should be applied to the managers of business firms. The view of most economists is that moral standards in business are not relevant, beyond the normal personal obligations to speak the truth and observe the law, because profit maximizing behaviour, under market and resource constraints, leads inexorably to social welfare optimization. The opposing view of most humanists is that modern markets are not competitive enough to be constraining, that profit maximization often leads to social harm, and that welfare benefits are unjustly distributed. The article examines the moral constructs in microeconomic theory and the ethical objections to that theory at both the pragmatic and theoretic levels, and concludes that inappropriate assumptions about the nature and worth of human beings in the economic paradigm require the use of moral standards for business decisions and actions.